The Adaptability of Career Decision-Making Profiles: Associations With Self-Efficacy, Emotional Difficulties, and Decision Status. (December 2013) - Gadassi, Reuma; Gati, Itamar; Wagman-Rolnick, Halleli
The present study investigated a new model for characterizing the way individuals make career decisions (career decision-making profiles [CDMP]). Using data from 285 students in a preacademic program, the present study assessed the association of the CDMP's dimensions with the Emotional and Personality-related Career decision-making Difficulties questionnaire, the Career Decision-making Self-Efficacy scale, and the individuals' decision status. The results suggest that comprehensive Information Gathering, analytic Information Processing, a more internal Locus of Control, much Effort Invested, less Procrastination, greater Speed of Making the Final Decision, less Dependence on Others, and less Desire to Please others were more adaptive in making career decisions. Contrary to our hypotheses, high Aspiration for an ideal occupation, and low Willingness to compromise were more adaptive for the decision-making process; no level of Consulting with others was particularly adaptive.